2021
DOI: 10.3389/fcosc.2021.631998
|View full text |Cite
|
Sign up to set email alerts
|

Transparency About Values and Assertions of Fact in Natural Resource Management

Abstract: Worldwide, unsustainable use of nature threatens many ecosystems and the services they provide for a broad diversity of life, including humans. Yet, governments commonly claim that the best available science supports their policies governing extraction of natural resources. We confront this apparent paradox by assessing the complexity of the intersections among value judgments, fact claims, and scientifically verified facts. Science can only describe how nature works and predict the likely outcomes of our acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 82 publications
0
25
0
Order By: Relevance
“…Proponents for such point to the 1999 population goal for wolves of 350 individuals in late winter. We have shown that number is a value judgment by a few individuals not a scientifically sound target (Treves et al, 2021). Therefore, the adequacy of state regulatory mechanisms seems fragile, for reasons detailed in SM1 for those interested in policy background.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Proponents for such point to the 1999 population goal for wolves of 350 individuals in late winter. We have shown that number is a value judgment by a few individuals not a scientifically sound target (Treves et al, 2021). Therefore, the adequacy of state regulatory mechanisms seems fragile, for reasons detailed in SM1 for those interested in policy background.…”
Section: Discussionmentioning
confidence: 96%
“…Proponents of wolf-killing argued that the state population goal of 350 wolves demands such swift reductions (Material S1), but evidence suggests that goal is a value judgment by a few individuals that was treated as if it were an output of a scientific model (Treves et al, 2021). Moreover, the model used suffers from scientific flaws, so its assumptions and predictions are dubious (Treves et al, 2021). Nevertheless, the goal was reaffirmed in February 2021 (Material S1).…”
Section: Discussionmentioning
confidence: 99%
“…Second, little information is available about reproduction for our study period. Wolf reproduction data is generally difficult to collect and the state census method used tends to confound pack size with past reproduction [ 46 , 47 ]. Third, we could not be confident about the legal quota when we analyzed data in Fall 2021 nor does anyone know the eventual death toll.…”
Section: Methodsmentioning
confidence: 99%
“…Although the prior literature would seem to guide decision-makers in Wisconsin to choose a Fall 2021 wolfs-hunt quota that would not change the population, the wide variation in estimates above and the novelty of a second wolf-hunt in a single year produces new and greater uncertainties than the literature addresses. Also, in a series of papers on wolf science and policy in Wisconsin, we have shown how omissions of a history of methodological changes in censuses, censoring the information available in the disappearances of marked wolves, and a lack of alternative management scenarios altogether could both distort wolf policy and mire the science in uncertainties due to methods [ 23 , 33 , 37 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even when effects are positive, planners must inform stakeholders about potential benefits. Transparency and sharing of information can work towards establishing the project as a "trusted messenger" (Vance-Borland and Holley, 2011;Treves et al, 2021) and consequently allow the project to foster its network towards the conservation goals.…”
Section: The Conservation Network In Translocationsmentioning
confidence: 99%